2013
DOI: 10.3389/fpls.2013.00285
|View full text |Cite
|
Sign up to set email alerts
|

The physiological resilience of fern sporophytes and gametophytes: advances in water relations offer new insights into an old lineage

Abstract: Ferns are some of the oldest vascular plants in existence and they are the second most diverse lineage of tracheophytes next to angiosperms. Recent efforts to understand fern success have focused on the physiological capacity and stress tolerance of both the sporophyte and the gametophyte generations. In this review, we examine these insights through the lens of plant water relations, focusing primarily on the form and function of xylem tissue in the sporophyte, as well as the tolerance to and recovery from dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 84 publications
(154 reference statements)
2
77
0
1
Order By: Relevance
“…Plant hydraulic failure (catastrophic loss of hydraulic conductivity) is one of the major and widespread mechanistic causes of drought-induced mortality (Anderegg et al 2012;Nardini et al 2014). Much research has investigated how plants avoid hydraulic failure by preventing formation and spread of catastrophic xylem embolism (Brodribb and Cochard 2009;Pittermann et al 2013). However, recent research suggests the existence of a spectrum of strategies ranging from 'resistance' to 'recovery', with some plants coming remarkably close to hydraulic failure, but recovering once xylem tension is partially or fully relaxed (Ogasa et al 2013;Martorell et al 2014).…”
Section: How Plants Avoid Mortality: Resistance and Recovery Strategiesmentioning
confidence: 99%
“…Plant hydraulic failure (catastrophic loss of hydraulic conductivity) is one of the major and widespread mechanistic causes of drought-induced mortality (Anderegg et al 2012;Nardini et al 2014). Much research has investigated how plants avoid hydraulic failure by preventing formation and spread of catastrophic xylem embolism (Brodribb and Cochard 2009;Pittermann et al 2013). However, recent research suggests the existence of a spectrum of strategies ranging from 'resistance' to 'recovery', with some plants coming remarkably close to hydraulic failure, but recovering once xylem tension is partially or fully relaxed (Ogasa et al 2013;Martorell et al 2014).…”
Section: How Plants Avoid Mortality: Resistance and Recovery Strategiesmentioning
confidence: 99%
“…When xylem sap tension exceeds the air-seeding threshold, air can be aspirated from an air-filled conduit into a functional water-filled conduit through perhaps a large, preexisting pore or one that is created by tension-induced membrane stress (Rockwell et al, 2014). Air seeding leads to cavitation and embolism formation, with emboli potentially propagating throughout the xylem network (Tyree and Sperry, 1988;Brodersen et al, 2013). So, on the one hand, pit membranes are critical to controlling the spread of air throughout the vascular network, while on the other hand, they must facilitate the efficient flow of water between conduits (Choat et al, 2008;Domec et al, 2008;Pittermann et al, 2010;Schulte, 2012).…”
mentioning
confidence: 99%
“…Transport in seedless vascular plants presents an interesting conundrum because, with the exception of a handful of species, their primary xylem is composed of tracheids, the walls of which are occupied by homogenous pit membranes (Gibson et al, 1985;Carlquist andSchneider, 2001, 2007; but see Morrow and Dute, 1998, for torus-margo membranes in Botrychium spp.). At first pass, this combination of traits appears hydraulically maladaptive, but several studies have shown that ferns can exhibit transport capacities that are on par with more recently evolved plants Watkins et al, 2010;Pittermann et al, 2011Pittermann et al, , 2013Brodersen et al, 2012). Certainly, several taxa possess large-diameter, highly overlapping conduits, some even have vessels such as Pteridium aquilinum and many species have high conduit density, all of which could contribute to increased hydraulic efficiency Pittermann et al, 2011Pittermann et al, , 2013.…”
mentioning
confidence: 99%
“…Resisting drought allowed these plants to invest more time and energy into growth and reproduction, overcoming the slow growth associated with DT. Less than 1% of the sporophytes of modern pteridophytes are desiccation tolerant (Pittermann et al, 2013). On the other hand, DT is widespread in the gametophytes of pteridophytes.…”
Section: Plant Evolution and Dtmentioning
confidence: 99%